Unshaken eaudiobook Ruth. - Rivers, Francine (Lineage of Grace, 2014)
Book three in the five-book biblical historical fiction series by the New York Times bestselling author of Redeeming Love and A Voice in the Wind . She gave up everything, expecting nothing, and God honored her. Meet Ruth , one of the five women in the lineage of Christ. Her loyalty—especially toward her mother-in-law Naomi—helped her to persevere in the face of tragedy, and God gave her a second chance at love. Readers will be encouraged by the truth that God will faithfully provide for His children even when all hope seems lost. Unshaken is book three in the popular Lineage of Grace series about five unlikely women who changed eternity. "Francine Rivers spins a tale that's not only true to history, but satisfying to the heart." — Romantic Times